Potential relationship between passive plantar flexor stiffness and sprint performance in sprinters. (July 2018) - Takahashi, Chieri; Suga, Tadashi; Ueno, Hiromasa; Miyake, Yuto; Otsuka, Mitsuo; Terada, Masafumi; Nagano, Akinori; Isaka, Tadao
Abstract: Objective: To investigate the relationship between passive planter flexor stiffness and sprint performance in sprinters. Design: Cross-sectional study. Participants: Fifty well-trained male sprinters (age: 20.7 ± 1.9 years, height: 175.6 ± 4.9 cm, weight: 66.7 ± 5.1 kg) were participated in this study. Their best personal times in a 100-m sprint ranged from 10.22 to 11.86 s (mean, 11.12 ± 0.43 s). Methods: Passive stiffness of the plantar flexors measured using a dynamometer system. Passive stiffness during passive dorsiflexion was calculated from the slope of the linear portion of the torque-angle curve. Results: Plantar flexor passive stiffness was significantly correlated with personal best 100-m sprint time ( r = −0.334, P = 0.018). Conclusion: The present findings suggest that although the relationship between plantar flexor passive stiffness and personal best 100-m sprint time was relatively minimal, a higher plantar flexor passive stiffness may be a potential factor for achieving superior sprint performance in sprinters. Therefore, in the clinical setting, measurement of passive planter flexor stiffness may be useful for assessing sprint performance. Highlights: A stiffer plantar flexors contributes to running performance in endurance runners. Passive plantar flexor stiffness related to sprint performance in sprinters. Passive stiffness may be a potential parameter for assessing sprint performance.